The relationship between self-concept and state-trait anxiety in peruvian university students - Guevara-Cordero, Claudia Karina (2020)
Anxiety is a public health problem that must be researched. Theoretically, self-concept is related to anxiety. Because of this, the aim of this study is to find the relationship between these two variables. In order to achieve it, a simple non-experimental, transversal and correlational research was designed. In this investigation, the State-Trait Anxiety State Scale and an adapted version of the Garley Self-concept Questionnaire were used. The sample consisted of 150 young university students from Lima, between the ages of 17 and 27, of both sexes. The results indicated significant relationship and different levels of the effect size from low, moderate and large between trait anxiety and the dimensions of self-concept (physical, social, familiar, intellectual, personal and control), but state anxiety was only significantly related to intellectual, personal and control dimensions of self-concept. Finally, the findings are discussed based on the background information, the theoretical basis and limitations, developing recommendations for future research.